Noise-induced hearing loss in farmworkers: a scoping review - Coco, Laura; Fried, Marisa; Loria, Obdulia; Vazquez, Lluvia; Ekonomo, Katherine; Sanchez, Gabriela; Keeney, Annie J.; Beseler, Cheryl L. (Frontiers in Public Health, 2025)
ObjectiveFarmworkers who have prolonged exposure to loud noise are at risk for disabling hearing loss. The objectives of this scoping review are to (1) identify and summarize the evidence on noise-induced hearing loss in farmworkers, (2) describe instruments used to evaluate hearing loss outcomes, (3) describe testing approaches and limitations, and (4) provide recommendations for future studies that seek to quantify hearing loss in this population.MethodsWe performed a systematic search of three electronic databases, PubMed, CINAHL, and Scopus, to identify articles related to noise-related hearing loss in farmworkers. Our search was guided by Arksey and O’Malley’s methodological framework and PRISMA-ScR guidelines.ResultsA total of 57 articles met inclusion criteria. The majority of studies were undertaken in North America (n = 32, 56%), and most were in the midwestern United States. Farmworkers tended to be white, male, and work in crop agriculture. A total of 47 studies (82%) used audiometry to measure farmworkers’ hearing sensitivity, among which testing was carried out at various locations, including hospitals, clinics, farmworkers’ homes, and worksites. The criteria for defining hearing loss varied across studies making it difficult to summarize results. Among 14 studies that used a cutoff point greater than 25 decibels, the prevalence of hearing loss ranged between 46 and 98%. Subjective outcomes (used in 14 studies) were typically assessed using a variety of researcher-developed questions. The prevalence of hearing difficulties in this category was as high as 87%.ConclusionHearing loss is prevalent across studies and does not appear to decrease over the years. Our findings call for more research among diverse farmworker populations. Further, given the high prevalence of hearing loss in many of the studies reviewed, there is clearly a need to develop strategies to protect farmworkers from noise exposure and noise-induced hearing loss.